Laboratory diagnosis of EB virus infection in some cases presenting as hepatitis. Issue 2 (February 1978) - Edwards, J M; Vandervelde, E M; Cohen, B J; McSwiggan, D A
Abstract : In 1975 and 1976, 7580 serum specimens were tested for HBsAg by the passive haemagglutination test, Hepanosticon. Serum from 38 people gave a positive result after absorption with the absorbent provided, but the presence of HBsAg could not be confirmed by other tests. Tests for current infection with EB virus, namely, the presence of heterophil antibody and EB virus specific IgM, were performed and were positive in 11 of the 38. In six of these the clinical picture was of hepatitis rather than infectious mononucleosis.